Co-exposures to physical and psychosocial work factors increase the occurrence of workplace injuries among French care workers - Colin, Régis; Wild, Pascal; Paris, Christophe; Boini, Stéphanie (Frontiers in Public Health, 2022)
Objective: The aim of this study was to analyse the effect of co-exposures to physical and psychosocial factors (PSF) regarding the incidence of workplace injuries (WI) among care workers. Additional objective was to identify the work factors associated with the co-exposure combinations leading to the highest rates of WI. Methods: The study sample consisted of 4 418 care workers participating to the French Working Conditions Survey both in 2013 and 2016. WI were assessed during the 4-year follow-up by matching the databases of the National Health Insurance Funds’ compensation system. We assessed exposure for physical factors and PSF using factorial analyses and hierarchical clustering. We implemented a Poisson regression model with the WI incidence as the outcome and the clusters as independent variables of interest. Logistic regression model allowed identifying the work factors that predicted co-exposure combinations with a WI rate of 40 ‰. Results: WI were highly related to both physical and psychosocial exposures. With low exposure to one or the other, there was no increased risk of WI. Physical factors and PSF potentiated each other and their co-exposure significantly increased the risk of WI, with model predicted rates per 1 000 persons-year for those most exposed to physical risk of 14.6 [4.5-24.8] with low PSF and 38.0 [29.8-46.3] with high PSF. Work factors that predicted co-exposure combinations with a rate of 40 WI‰ were: working as nursing assistant or hospital services officer, lack of predictability and flexibility of schedules, overtime, controlled schedules, work-family imbalance and insufficient preventive measures. Conclusions: Our findings highlight the need to take into account psychosocial factors in addition of only considering physical factors when analysing WI occurrence, as usually done. Prevention actions must be taken to reduce both physical and psychosocial exposure. These results provide keys points for the prevention of WI among care workers.